The origin of a primordial genome through spontaneous symmetry breaking - Nobuto Takeuchi (Nature Portfolio, 2017)
Early molecules of life likely served both as templates and catalysts, raising the question of how functionally distinct genomes and enzymes arose. Here, the authors show that conflict between evolution at the molecular and cellular levels can drive functional differentiation of the two strands of self-replicating molecules and lead to copy number differences between the two.